Risk Factors and Options to Improve Engraftment in Unrelated Cord Blood Transplantation - Anna D. Petropoulou; Vanderson Rocha (Hindawi Limited, 2011)
Use of umbilical unrelated cord-blood (UCB) cells as an alternative source of hematopoietic cell transplantation has been widely used mainly for patients lacking an HLA-matched donor. UCB present many advantages over bone marrow or mobilized peripheral blood from volunteer donors, such as rapid availability, absence of risk for the donor, and decreased incidence of acute graft-versus-host disease. However, a significant clinical problem is delayed engraftment that is directly correlated with the number of hematopoietic stem cells in a cord-blood unit. The identification of prognostic factors associated with engraftment that can be easily modified (e.g., strategies for donor choice) and the development of new approaches including use of multiple donors, intrabone injection of UCB, ex vivo expansion, and cotransplantation with accessory cells are of crucial importance in order to circumvent the problem of delayed engraftment after UCB transplantation. Those approaches may increase the quality and availability of UCB for transplantation.